Potentials and Limitations of Bilingual Children’s Storybooks for Javanese Language Revitalization: A Case Study of The East Java Language Center - Musrifah Musrifah; Intihaul Khiyaroh (Journal of linguistics, culture and communication, 2026)
This study critically examines the potentials and limitations of a bilingual (Javanese-Indonesian) children’s storybook program as a strategy for Javanese language revitalization, using the initiative by the East Java Language Center as a case study. The decline of Javanese among the younger generation, particularly in urban areas, has reached a stage of cultural distortion, necessitating deliberate revitalization efforts. Employing a qualitative instrumental case study design, this research draws on documentary analysis of institutional social media, semi-structured interviews with program coordinators and selected authors, and participant observation as a contesting writer. Data were analyzed thematically using Wallace’s revitalization theory and Fishman’s framework of intergenerational language transmission. The findings reveal that the program systematically follows key revitalization stages: basic planning, material development, readability testing, digitalization, and school-based implementation. Bilingual storybooks integrate local Javanese cultural values, STEAM content, and attractive illustrations, making the language more accessible to children aged 7–13 years. However, critical limitations are identified, including a low manuscript acceptance rate (20%), absence of quantitative readability test results, lack of impact evaluation data, and unresolved digital divides in rural areas. Digital formats (flipbooks, audiobooks) remain underutilized without proven effectiveness. Braille versions and deaf community involvement demonstrate promising inclusivity practices. This study contributes a balanced model for language revitalization through bilingual children’s literature and recommends longitudinal impact studies and teacher-parent empowerment for sustainable intergenerational transmission.